Perancangan Interior Pusat Kegiatan Kreatif dan Hiburan Keluarga di Surabaya - F Gunawan, Natasha (Intra, 2014)
People who live in big cities tend to have more complex and higher demand of life than those who live in a small town. Condition that causes them easily once exposed to a lot of pressure. High level of education and lifestyle that causes people to feel tired easily and always look forward to something new and present in their city. This interior design of creative activities center and family entertainment is realizing itâs potential as an alternative recreational activity that is needed by the majority of the big cities which already saturated with recreational activities that have long existed and flourished. There are facilities on offer such as wide variety of creative activities, private room to hold a variety of special events and activities, cafe, snack corner, retail, waiting and reading area along with the lobby and popular art & craft classes which have previously known by the people of Surabaya such as scrapbooking, paper quilling, knitting and crochetting.